Potential Distribution of Chagas Disease Vectors (Hemiptera, Reduviidae, Triatominae) in Colombia, Based on Ecological Niche Modeling (2016)
Triatomines (Hemiptera, Reduviidae) are hematophagous insects that are considered important vectors of Trypanosoma cruzi.They arewidely distributed in Americawith rare occurrences in Eastern Asia, though they are primarily found in the Neotropical region. Disease transmission occurs from southernUnited States to Argentina, with approximately 25% of the human population at risk. Triatomines have a wide range of climatic and ecological tolerability because they inhabit diverse ecosystems, from humid to dry forests across the Americas. They are found at different altitudes and have high vagility, which allows them to exploit diverse food resources and to find different resting sites, including intra- and peridomiciliary habitats. Therefore, at the species level, habitat preferences are influenced by environmental factors, which can strongly control efforts. Ecological niche models are empirical or mathematical estimates of species ecological niche in terms of suitable habitat conditions. They permit the association of different ecogeographical variables (e.g., environmental, topographical, and anthropogenic) with the species distribution, by identifying the variables that constrain and define the particular niche. The modeling outcome can be a spatial representation of the favorable habitat for a species occurrence. Therefore, suitability maps for the species, as function of their ecological niche, can be created.